Salt-affected soils, reclamation, carbon dynamics, and biochar: a review - Amini, Sevda; Ghadiri, Hossein; Chen, Chengrong; Marschner, Petra (Journal of soils and sediments, 2016)
PURPOSE: This paper reviews chemical, physical, and biological problems of salt-affected soils and different reclamation methods applied to rehabilitate these soils. METHODS: Methods to increase C stocks in these lands are discussed with a focus on biochar application as a potential new approach to not only to increase the C content but also to improve soil properties. Gaps in research knowledge in this field are then identified. RESULTS: Given the concern on the continued worldwide expansion of salt-affected lands and the focus on C sequestration processes, this review has evaluated current knowledge on salt-affected soils and their remediation with organic materials and plants. The review of the published literature has highlighted important gaps in knowledge, which limit our current understanding of rehabilitation of salt-affected soils with organic amendments specially biochar and the associated carbon dynamic. Knowledge about application of biochar in salt-affected soils is scant, and to date, most studies have evaluated biochar use only in nonsalt-affected soils.